2006
DOI: 10.1155/2006/435028
|View full text |Cite
|
Sign up to set email alerts
|

Internet‐Based Asthma Education ‐‐ A Novel Approach to Compliance: A case Report

Abstract: Asthma costs Canadians over $1.2 billion per annum and, despite advances, many asthmatic patients still have poor control. An action plan, symptom diary and measurement of peak expiratory flow have been shown to improve clinical outcomes. Effective educational interventions are an important component of good care. However, many rural sites lack not only access to education but physician care as well. It is reasonable, therefore, that an Internetbased asthma management program may be used as an approach. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…Researchers considered the mean difference = 0.5 in Juniper's Asthma Quality of Life Questionnaire and determined that patient education had a clinically important role for improving the quality of life (McLean et al., 2010). Other studies have shown consistent results similar to our findings (Ahmed et al., 2016; Chan, Callahan, Sheets, Moreno, & Malone, 2003; O'hara, Vethanayagam, Majaesic, & Mayers, 2006; Tavakoli, Alipouran, & Zarei, 2018). However, no other study has examined the effects of offering patient education through Telegram for asthmatic adolescents.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Researchers considered the mean difference = 0.5 in Juniper's Asthma Quality of Life Questionnaire and determined that patient education had a clinically important role for improving the quality of life (McLean et al., 2010). Other studies have shown consistent results similar to our findings (Ahmed et al., 2016; Chan, Callahan, Sheets, Moreno, & Malone, 2003; O'hara, Vethanayagam, Majaesic, & Mayers, 2006; Tavakoli, Alipouran, & Zarei, 2018). However, no other study has examined the effects of offering patient education through Telegram for asthmatic adolescents.…”
Section: Discussionsupporting
confidence: 92%
“…For diabetic patient education, Tavakoli et al., (2018) showed that educational messaging through Telegram could improve the perception constructs by using the health belief model (HBM) and emphasizing the self‐care behaviours. Similarly, O'hara et al., (2006) showed that Internet‐based education for asthma management can reduce the need for emergency intervention and stabilizing control, even when travelling to another location. McLean et al., (2010) reviewed 21 research articles in a wide range of technologies aimed at the impact of distance learning and reported that virtual interventions did not clinically improve the QoL for asthmatic patients, and these results show clinical improvement in scores of two domains for the QoL (activity limitation and asthma symptoms) and do not include the scores of emotion domains in two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Asthma education has the potential to be delivered online; however, to date, most of these self-management tools have included the monitoring of symptoms and the involvement of healthcare professionals such as the patient's physician or an asthma nurse (12)(13)(14)(15)(16)(17)(18)(19)(20). Some of these interventions have shown improvements in asthma control (13,14,20) and lung function (20), but little change in quality of life (20) or asthma exacerbations (20).…”
Section: Introductionmentioning
confidence: 99%